2019
DOI: 10.1111/cas.14248
|View full text |Cite
|
Sign up to set email alerts
|

GTF2IRD1 on chromosome 7 is a novel oncogene regulating the tumor‐suppressor gene TGFβR2 in colorectal cancer

Abstract: Chromosome 7q (Ch.7q) is clonally amplified in colorectal cancer (CRC). We aimed to identify oncogenes on Ch.7q that are overexpressed through DNA copy number amplification and determine the biological and clinical significance of these oncogenes in CRC. We identified general transcription factor 2I repeat domain-containing protein 1 (GTF2IRD1) as a potential oncogene using a CRC dataset from The Cancer Genome Atlas with a bioinformatics approach. We measured the expression of GTF2IRD1 in 98 patients with CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…And previous study by Huo et al reported that GTF2IRD1 overexpression correlates with poor survival in patients with breast cancer, lung cancer, and ovarian cancer [ 11 ]. Additional study by Nambara et al also identified GTF2IRD1 as an oncogene and unfavorable prognostic factor in colorectal cancer [ 8 ]. These findings strongly suggest that GTF2IRD1 is a potential oncogene and unfavorable prognostic biomarker in human cancers, including PC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…And previous study by Huo et al reported that GTF2IRD1 overexpression correlates with poor survival in patients with breast cancer, lung cancer, and ovarian cancer [ 11 ]. Additional study by Nambara et al also identified GTF2IRD1 as an oncogene and unfavorable prognostic factor in colorectal cancer [ 8 ]. These findings strongly suggest that GTF2IRD1 is a potential oncogene and unfavorable prognostic biomarker in human cancers, including PC.…”
Section: Discussionmentioning
confidence: 99%
“…However, early study by Hasegawa et al suggested that GTF2IRD1 represses adipose tissue fibrosis through inhibiting TGF-β signaling pathway [ 24 ]. Besides, Nambara et al reported that GTF2IRD1 overexpression might result in inhibition of TGF-β signaling pathway in colorectal cancer [ 8 ]. These results suggest the tissue specificity of GTF2IRD1 in regulating TGF-β signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Based on insight from previous findings and our multiregional genomic analysis, we have identified novel oncogenes, including elF5-mimic protein 1 (5MP1), DEAD-Box Helicase 56 (DDX56), and general transcription factor 2I repeat domain-containing protein 1 (GTF2IRD1), located on amplified chromosome 7 in CRC. [17][18][19] Therefore, we focused on genes that were overexpressed due to gene amplification as potential therapeutic targets in PDAC, because these genes can be targeted with gene-specific medicines, including neutralizing antibodies or small chemicals.…”
mentioning
confidence: 99%